Policy and infrastructure for information technology. - MUNASINGHE, Mohan (1995)
Develops an integrated policy framework to address specific national goals and incorporate information technology within important economic sectors and activities at all levels. Identifies issues and constraints in developing countries, and suggests a more effective implementation strategy.